Because I’m Happy—An Overview on Fostering Positive Emotions Through Virtual Reality - Pavic , Katarina; Vergilino-Perez , Dorine; Gricourt, Thierry; Chaby, Laurence (Frontiers in Virtual Reality, 2022)
In recent years, an increased demand for improving mental health and well-being led to developing procedures capable of enhancing positive experiences. One highly attractive candidate for evoking positive experiences in order to foster well-being is Virtual Reality (VR), as VR enables users to experience various situations in controlled and safe environments. This review first provides an overview of how positive emotions, well-being and VR are interconnected. Then, VR’s potential for eliciting positive emotional states and leveraging well-being in young, elderly, healthy or vulnerable users is discussed. Methodological and ethical considerations about VR technology, video contents, user characteristics and measurements of VR’s efficacy are reviewed. It emerges that VR is highly efficient in inducing positive emotions in various users and settings. The main applications of positive VR experiences consist in using VR for relaxation, motivation for physical activities, stress and pain management and apathy treatment. Although VR is efficient in eliciting positive emotions and experiences, the underlying operating mechanisms remain unclear and are yet to be further investigated. Finally, concerns about the need for a broader reflection on user implication when designing VR experiences, clear guidelines for VR use in clinical settings, and the repercussions of inducing positive emotions through technology are raised.